Human resource management practices on organisational commitment: the Islamic perspective - Hashim, Junaidah (Emerald Group Publishing Limited, 2010)
Purpose – Islam urges all Muslims to perform their utmost best when they work. Giving the best requires full commitment. Employees’ commitment is influenced by many factors, including the management styles within the organisation. This paper aims to examine the management of human resources from the Islamic perspective and its effects on organisational commitment among selected employees in Islamic organisations in Malaysia. Design/methodology/approach – The study employed a self-developed questionnaire that was personally distributed to employees. In total, 121 Muslim employees who work in various positions in eight Islamic organisations participated as respondents of this study. Findings – The findings revealed that the selected organisations frequently practise the Islamic approach in all its human resource management (HRM) functions. The results of correlation and regression analysis show that the Islamic approach in HRM was highly and significantly correlated to organisational commitment. About 45 per cent of the organisational commitment variance was explained by the Islamic approach in HRM. Practical implications – An introduction to the Islamic approach in HRM practices is an initial attempt to provide managers with an effective way of managing and understanding the people they work with. This knowledge would be useful to even non-Muslim managers. For Muslim human resource managers, it is essential for them to not only know but also to apply the Islamic approach in managing employees. Non-Muslim managers will have a better understanding of the expected behaviours of their Muslim employees. Muslim employees regardless for who they work are expected to be honest, trustworthy, and determined to continuously strive for the best. Originality/value – This study is unique from other previous studies. Instead of discussing Islamic management in general, this study explores in-depth every function of HRM based on authentic Islamic sources, as well as providing empirical evidence.